A blinded randomized controlled trial evaluating the efficacy of chitosan gel on ostial stenosis following endoscopic sinus surgery. Issue 7 (16th January 2013) - Ngoc Ha, Thanh; Valentine, Rowan; Moratti, Stephen; Robinson, Simon; Hanton, Lyall; Wormald, Peter‐John
<x xml:space="preserve">Abstract</x> Background Stenosis of sinus ostia following endoscopic sinus surgery (ESS) is the most common reason for revision surgery. Chitosan‐dextran (CD) gel has been shown to be an effective hemostatic agent; however, its effects on ostial stenosis are unknown. This study aims to quantify the effect of CD gel on circumferential scarring following ESS. Methods A prospective, blinded, randomized, controlled trial was conducted in 26 patients undergoing ESS. Measurements of neo‐ostia were taken using a standard‐sized measuring probe. CD gel was applied unilaterally, while contralateral sides received no gel. Ostial diameters were measured by a blinded observer at 2, 8, and 12 weeks postoperation. Sinus ostial areas calculated as a proportion of the original were compared for each ostium at each time point. Results Intraoperative ostial areas were comparable for CD gel and control sides (38 mm2 vs 39 mm2, 131 mm2 vs 120 mm2, and 203 mm2 vs 193 mm2, in frontal, sphenoid, and maxillary ostia, respectively; p > 0.05). CD gel significantly improved sinus ostial patency. The largest difference was seen when ostial areas at 12 weeks were compared with their corresponding baseline areas (66% vs 31% frontal, p < 0.001; 85% vs 47% sphenoid, p < 0.001; and 74% vs 54% maxillary ostia, p = 0.002). The difference between raw ostial areas reached statistical significance in sphenoid (p < 0.001) and maxillary (p = 0.01), but not in frontal ostia (p > 0.05) at 12 weeks. Conclusion CD gel produced significantly less stenosis of all neo‐ostia following ESS and may reduce the necessity for revision surgery in patients with chronic rhinosinusitis.